La contingence des faits linguistiques : réflexions sur la variation et le changement - Pierre Larrivée (Corela)
This paper is a reflection on the role of contingent facts for the general understanding of language. Such facts are illustrated by the lacks of proportionality in the paradigm of French indefinites and the irregular correlations between the Null Subject Parameter and other hypothesised parameters. Such contingencies clearly go against the expectation raised by at least some versions of structuralism and the current chomskyan Minimalist Program. As demonstrated by alternative views being developed in various natural and social sciences, and as shown by recent research on formulaic language, contingency may be understood as the result of the expedient character of a medium geared towards action. A view of language as action may thus offer a perspective able to account both for the general default rules shaping a grammar and for the contingencies that entrench them in use, as both are integral and complementary aspects of language.